In Situ Grown CoMn2O4 3D‐Tetragons on Carbon Cloth: Flexible Electrodes for Efficient Rechargeable Zinc–Air Battery Powered Water Splitting Systems. Issue 47 (22nd October 2021) - Janani, Gnanaprakasam; Surendran, Subramani; Choi, Hyeonuk; Han, Mi‐Kyung; Sim, Uk
Abstract: The integration of energy conversion and storage systems such as electrochemical water splitting (EWS) and rechargeable zinc–air battery (ZAB) is on the vision to provide a sustainable future with green energy resources. Herein, a unique strategy for decorating 3D tetragonal CoMn2 O4 on carbon cloth (CMO–U@CC) via a facile one‐pot in situ hydrothermal process, is reported. The highly exposed morphology of 3D tetragons enhances the electrocatalytic activity of CMO–U@CC. This is the first demonstration of such a bifunctional activity of CMO–U@CC in an EWS system; it achieves a nominal cell voltage of 1.610 V @ 10 mA cm −2 . Similarly, the fabricated rechargeable ZAB delivers a specific capacity of 641.6 mAh gzn −1, a power density of 135 mW cm −2, and excellent cyclic stability (50 h @ 10 mA cm −2 ). Additionally, a series of flexible solid‐state ZABs are fabricated and employed to power the assembled CMO–U@CC‐based water electrolyzer. To the best of the authors' knowledge, this is the first demonstration of an in situ‐grown binder‐free CMO–U@CC as a flexible multifunctional electrocatalyst for a built‐in integrated rechargeable ZAB‐powered EWS system. Abstract : Flexible 3D CoMn2 O4 is grown on carbon cloth by a facile in situ hydrothermal method. The controlled tetragonal morphology of CMO‐U@CC reveals high exposure of active surface area and electronic conductivity. The multifunctional electrode with improved kinetics boosts the electrocatalytic activities (ORR, OER, and HER) to integrate the rechargeable zinc–air battery and water splitting systems.